Photocatalytic antibacterial properties of copper doped TiO2 prepared by high-energy ball milling. Issue 10 (July 2020) - Wang, Mei; Zhao, Qianfei; Yang, He; Shi, Dai; Qian, Juncen
Abstract: TiO2 nanopowders and Cu-doped TiO2 were prepared by high-energy ball milling and characterized by X-ray diffraction (XRD), UV–vis diffuse reflectance (UV–vis - DRS) spectra, a scanning electron microscope (SEM), an energy dispersive spectrum (EDS) and an X-ray photoelectron spectrometer (XPS) to study the effect of Cu doping amount, milling time and balls-to-powder ratio on the microstructure and antimicrobial activity of the nanopowders. The results show that the mean size of the powders is reduced to below 100 nm after 3 h of milling. The prepared copper-doped TiO2 powders have excellent antibacterial activity against the Gram bacteria, which depends on the degree of copper doping.